Raoultella planticola and urinary tract infection: The first laboratory-confirmed case in an HIV-infected patient in Mali. - Yacouba Cissoko; Aminata Maiga; Djeneba Dabitao; Mariam S Dicko; Drissa Koné; Issa Konaté; Jean-Paul Dembele; Assetou F Sidibe; Ibrahima I Maiga; Sounkalo Dao (Journal of Infection in Developing Countries)
Raoultella planticola is a Gram-negative, aerobic, non-motile bacterium, abundant in the environment, but rarely associated with pathology in humans. Notably, few urinary tract infections caused by R. planticola have been reported. To our knowledge, we are presenting here the first case of urinary tract infection caused by R. planticola in an HIV-infected individual. It is a 50-year-old female, with a history of HIV-1 infection treated for three years. At admission, her CD4 count was 70 cells/mL, and the main complaints were severe diarrhea and cough. She was diagnosed and treated for pulmonary tuberculosis (TB) and E. Coli enteritis. Initially, we observed a good evolution. However, on day 21 of hospitalization, she presented with fever and dysuria. Urinalysis revealed the presence of R. planticola with resistance to multiple antibiotics. We also detected that she has an HIV-2 but not HIV-1 infection. After receiving the right regimen, she was confirmed cured of her bacterial infections.